A case report: Giant intra-abdominal liposarcoma presenting acute renal failure - Duman, Kazim; Girgin, Mustafa; Artas, Gokhan (Elsevier Sci Ltd, 2016)
Introduction: Liposarcomas represent 20-30% of adult soft tissue tumors and its abdominal localization occurs only in 5% of cases. Most are asymptomatic, but few present with abdominal mass and pain, fatigue, nausea, vomiting. They infiltrate adjacent organs and cause intestinal obstruction, intestinal ischemia-perforation, hydronephrosis, ureteric fistula and even aortic rupture. Here we aimed to report a rare case of a giant liposarcoma which originated from mesentery. Presentation of case: A 45-year-old male presented with slightly abdomen distention, urinary retention, oliguria since fifteen days. There was no concomitant nausea, vomiting and lower extremity edema. We found renal function tests abnormal. Contrast-enhanced computed tomography (CT) demonstrated a 20 X 18 cm, well-circumscribed, lobulated, heterogeneous mass. Both ureters were compressed by the mass. The entire mass was totally excised. After the operation, the patient's renal function returned to normal levels dramatically. The tumor was diagnosed as dedifferentiated liposarcoma. Discussion: In cases of intra-abdominal mass is detected, surely abdominal compartment syndrome (ACS) should be considered. If vital signs, pulmonary function tests (PFT) and value of the CVP are abnormal, intra-abdominal pressure should be measured. Our findings mentioned above were not observed. Conclusion: A detailed history should be obtained other abdominal solid organs should also be considered while performing a careful physical examination, the amount of urinary output in particular should be questioned and this sytemic questioning should be supported by specific laboratory tests. (C) 2016 The Authors. Published by Elsevier Ltd on behalf of IJS Publishing Group Ltd.
Keywords: Giant liposarcoma; Acute renal failure; Intra-abdominal localization